2021
DOI: 10.11591/ijeecs.v22.i1.pp534-541
|View full text |Cite
|
Sign up to set email alerts
|

Air temperature prediction using different machine learning models

Abstract: Air temperature is an essential climatic component particularly in water resources management and other agro-hydrological/meteorological activities planning This paper examines the prediction capability of three machine learning models, least square support vector machine (LSSVM), group method and data handling neural network (GMDHNN) and classification and regression trees (CART) in air temperature forecasting using monthly temperature data of Astore and Gilgit climatic stations of Pakistan. The prediction ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…700 Because the prediction of TEG generated energy directly depends on temperature differentials, methods for predicting air temperature are suitable for application in this area. Air temperature also represents an essential climatic parameter in water resource management and other agro-hydrological/ meteorological activities [95]. To forecast air temperatures, neural networks (NN) and support vector machines (SVM) are widely implemented [96].…”
Section: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…700 Because the prediction of TEG generated energy directly depends on temperature differentials, methods for predicting air temperature are suitable for application in this area. Air temperature also represents an essential climatic parameter in water resource management and other agro-hydrological/ meteorological activities [95]. To forecast air temperatures, neural networks (NN) and support vector machines (SVM) are widely implemented [96].…”
Section: Environmentmentioning
confidence: 99%
“…Neural network approaches are suitable for air temperature prediction because they have fast computing speeds and are capable of solving complex problems [101]. Many types of approach are based on NNs, for example, Cascade Forward NN, Feed Forward NN [97], Group method of data handling NN [95], Deep Belief Network [99], and Generalised Regression NN [100], and can be applied to air temperature forecasting. Neural networks methods are combined with optimisation approaches such as Artificial NN and genetic algorithms [98].…”
Section: Environmentmentioning
confidence: 99%
“…Machine learning algorithms, especially classification algorithms are utilized for similar to human activity recognition. Some of the significant problems addressed using the machine learning algorithms are: detecting malicious links from world wide web (www) [21], handwritten digit recognition [22], depression detection from image and video analysis [23], air temperature prediction [24], etc. Therefore, we have applied seven different classification algorithms namely, logistic regression, random forest, K-nearest neighbor (k-NN), Support vector machine (SVM), Gradient Boosting, Convolutional Neural Network (CNN), Bi-directional LSTM.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results demonstrate that the K-closest neighbor method performs better than other models. Adnan et al [5] examined three prediction models including least square support vector machine (LSSVM), classification and regression trees (CART) and group method and data handling neural network (GMDHNN) to forecast air temperature based on monthly temperature data from Pakistan. The finding was indicated that the LSSVM model is more accurate in temperature forecasting than the other two models.…”
Section: Introductionmentioning
confidence: 99%